Etanercept maintains the clinical benefit achieved by infliximab in patients with rheumatoid arthritis who discontinued infliximab because of side effects - Iannone, Florenzo (BMJ Group, 2007)
OBJECTIVE: To evaluate the efficacy of switching to etanercept treatment in patients with rheumatoid arthritis who already responded to infliximab, but presented side effects. METHODS: Charts of 553 patients with rheumatoid arthritis were retrospectively reviewed to select patients who responded to the treatment with infliximab and switched to etanercept because of occurrence of adverse effects. Clinical data were gathered during 24 weeks of etanercept treatment and for the same period of infliximab treatment before infliximab was stopped. Disease Activity Score computed on 44 joints (DAS‐44), erythrocyte sedimentation rate (ESR) 1st hour, Visual Analogue Scale (VAS) of pain, Health Assessment Questionnaire (HAQ), and C reactive protein (CRP) were assessed every 8 weeks. RESULTS: 37 patients were analysed. Adverse events to infliximab were mostly infusion reactions. No statistically significant difference between infliximab, before withdrawal, and etanercept, after 24 weeks, was detected in terms of DAS‐44 (2.7 and 1.9, respectively), HAQ (0.75 and 0.75, respectively), ESR (21 and 14, respectively) and CRP (0.5 and 0.3, respectively). VAS pain decreased significantly after switching to etanercept treatment (40 and 24, respectively; p<0.05). CONCLUSIONS: Our study shows that etanercept maintains the clinical benefit achieved by infliximab, and suggests that a second tumour necrosis factor (TNF) α inhibitor can be the favourable treatment for rheumatoid arthritis when the first TNFα blocker has been withdrawn because of adverse events.